The Efficacy and Tolerability of a Fixed Combination Clindamycin (1.2%) and Benzoyl Peroxide (3.75%) Aqueous Gel in Adult Female Patients with Facial Acne Vulgaris - Zeichner, Joshua A. (J Clin Aesthet Dermatol, 2015)
Objective: To investigate the efficacy and tolerability of clindamycin phosphate 1.2%/benzoyl peroxide 3.75% gel or vehicle monotherapy in adult female acne patients. Methods: A post hoc analysis in 72 adult female patients (aged ≥25 years) with moderate-to-severe acne receiving clindamycin phosphate 1.2%/benzoyl peroxide 3.75% gel or vehicle for 12 weeks. Results: The efficacy of clindamycin phosphate 1.2%/benzoyl peroxide 3.75% gel was significantly greater than vehicle. The mean percent change from baseline in inflammatory and noninflammatory lesion counts and the percentage of patients who achieved a 2-grade reduction in the Evaluator’s Global Severity Score was 68.7%, 60.4, and 52.7 percent, respectively (P=0.019, 0.020 and 0.074 versus vehicle). In addition, 44 percent of patients reported their acne to be “clear” or “almost clear” at Week 12 (P=0.026 versus vehicle). No substantive differences were seen in cutaneous tolerability among treatment groups, and no patients discontinued treatment because of adverse events. Limitations: It is not possible to determine the contributions of the individual active ingredients, and this study was not set up specifically to investigate the treatment of adult female acne. Conclusion: Clindamycin phosphate 1.2%/benzoyl peroxide 3.75% gel provides statistically significant greater efficacy than vehicle in treating acne in adult female patients and has a favorable safety and tolerability profile.